Dose-Effect/Toxicity of Bupleuri Radix on Chronic Unpredictable Mild Stress and Normal Rats Based on Liver Metabolomics - Wang, Peng; Gao, Xiaoxia; Liang, Meili; Fang, Yuan; Jia, Jinping; Tian, Junsheng; Li, Zhenyu; Qin, Xuemei (Frontiers in Pharmacology, 2021)
Depression, one of the most prevalent psychiatric diseases, affects the quality of life of millions of people. Studies have shown that the lower polar fraction of Bupleuri Radix (PBR) elicited therapeutic effects in chronic unpredictable mild stress (CUMS) rats. In contrast, comparatively mild liver injury was observed in normal rats administered a high PBR dose. It is essential to clarify the effective and safe dose of PBR and its dose-effect/toxicity relationship. In this study, we used the CUMS model to evaluate the effects and toxicities of PBR and to decipher the dose-effect/toxicity relationships and mechanism by using the liver metabonomics combined with multivariate statistical analysis. In CUMS rats, PBR improved the depression-like behaviors including the reduced body growth rate, anhedonia, and locomotor activities, and markedly reduced alanine aminotransferase (ALT) and aspartate aminotransferase (AST). In control rats, PBR treatment altered ALT and AST from typical levels. Moreover, the effective dose range for CUMS rats was 12.6 - 163 g/kg, the median toxicity dose for CUMS and normal rats were 388 g/kg and 207 g/kg. The toxicological results showed that the cytokeratin-18 fragment level was increased significantly in CUMS rats given with 100 g/kg PBR. After a comprehensive analysis, the use of PBR dose was determined to be 12.6–50 g/kg. In CUMS rats, PBR could reverse amino acid metabolism, energy metabolism, sphingolipid metabolism, and β-oxidation of fatty acids to produce an anti-depressant effect in a dose-dependent manner. In control rats, two additional metabolic pathways were significantly perturbed by PBR, including glycerophospholipid metabolism and bile acid metabolism. Moreover, the comprehensive metabolic index including dose-effect index (DEI) and dose toxicity index (DTI) had a remarkable ability (ROC=0.912, ROC=0.878) to predict effect and toxicity. The DEI and DTI were used to determine the dose range of effect and toxicity which was shown high concordance with previous results. Furthermore, the CUMS rats possessed a higher toxicity tolerance dose of PBR which was consistent with the theory of "You Gu Wu Yun" in traditional Chinese medicine. The metabonomics techniques combined with correlation analysis could be used to discover indicators for comprehensive evaluations of efficacy and toxicity.